MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL COOPERATIVE LEARNING TIPE NUMBERED HEADS TOGETHER PADA MATERI SISTEM PEREDARAN DARAH MANUSIA DI SDN KAMPUNG SAWAH KOTA BOGOR - Yeti Hidayati (Journal of Social Studies, Arts and Humanities (JSSAH), 2021)
IMPROVING STUDENT LEARNING OUTCOMES THROUGH COOPERATIVE LEARNING MODEL NUMBERED HEADS TOGETHER IN THE MATERIAL OF THE HUMAN CIRCULATORY SYSTEM IN ELEMENTARY SCHOOLS (SDN KAMPUNG SAWAH KOTA BOGOR)The low science learning outcomes are due to students learning only relying on the teacher as the only source of learning, students really depend on the teacher. Learning interactions occur in one direction, students feel afraid if the answers are not the same, new ideas or ideas do not develop, are afraid to ask questions because they are worried that the questions will not hit. Often students do not appreciate the ideas, opinions of their friends, and are lazy to read source books / subject matter. The classroom atmosphere is really calm, orderly, quiet, passive, so that innovation and creativity become deadlocked. This has an impact on student learning outcomes whose average value is still much below the Minimum Completeness Criteria (80). The purpose of Classroom Action Research through the cooperative learning model of Numbered Heads Together type is to improve science learning outcomes on the material of the human circulatory system in class V-A Elementary School (SDN Kampung Sawah, Bogor City). Besides, it also wants to know the teacher's skills in using the model and type of learning in improving science learning outcomes on the material of the circulatory system. Implemented in 2 cycles, one cycle consists of two meetings. The results of this study show that in the initial test (pre-cycle) the average value is only 65.00, the average completeness in the first cycle of action 1 is 69.00, the second action is 77.00 and the average completeness of the second cycle of action is 1 79.00, action 2 86.00 included in the very good category. Absorption and Completeness Learning outcomes in the initial test (pre-cycle test) before the action was taken were 20%, the first cycle showed the absorption and completeness of the class to be 31.43% and 57.14%, while in the second cycle the absorption and completeness of the class increased rapidly to 71.43% and 94.29% which are in the very high category. The results of the study can be concluded that through the cooperative learning model Numbered Heads Together type can improve science learning outcomes for students in class V-A in elementary school (SDN Kampung Sawah, Bogor City).